To study the difference of serum Vitamin D3 level and calcium profile in childhood multitransfused beta-thalassemia major between children receiving chelation therapy and those not receiving chelation therapy in a tertiary care hospital, Kolkata - Shah Masud Hayder; Shabarna Roy; Neha Karar; Dipanjan Halder; Rijwoana Aktar (Asian Journal of Medical Sciences, 2025)
Background: Most cases of beta-thalassemia major in children are associated with potentially severe clinical characteristics such as poor growth, feeding difficulties, hepatosplenomegaly, bone metabolic disorders, and skeletal abnormalities. Aims and Objectives: In our study, we evaluated the demographic and clinical presentations with the serum ferritin level, serum calcium, serum Vitamin D3 level, and serum phosphate level of 85 patients who received blood transfusions at regular intervals. Materials and Methods: We recruited children with beta-thalassemia major, confirmed by hemoglobin electrophoresis, for this study. We recorded the demographic details and blood transfusion status. We estimated serum ferritin, serum Vitamin D3 level, serum calcium, and serum PO4 using Enzyme-linked immunosorbent assay. Results: Of the 85 patients, 71 started chelation and 14 refused. 72 were non-consanguineous, and 13 were consanguineous offspring. 66% of the total patients had ferritin levels exceeding 1000 ng/mL. Marriage types did not show a significant association with ferritin. After 20 infusions, coagulation began at 83.53%. A significant link exists between chelation therapy and total transfusions. Nearly 40% of children (47.06%) had calcium levels <8 mg/dL. 23 (27.06%) of the 85 patients exhibited hypophosphatemia. Conclusion: In most people, chemotherapy does not impact their serum PO4 levels. We have found a significant association between frequent red cell transfusions during chelation therapy and increased levels of ferritin, Vitamin D3, calcium, and phosphate.